2010
DOI: 10.1080/13611267.2010.492945
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Undergraduate Researchers: An Exploratory Study of Students’ and Professors’ Perceptions

Abstract: Mentoring is believed to be one of the most influential factors in US efforts to encourage college-aged students to seek careers in science, yet the role that mentoring plays in this process has not been elucidated. The researchers were interested in understanding whether the long-held beliefs about the importance of mentoring would be revealed as what actually occurs in an undergraduate research program. They describe students' perceptions of the mentoring process and students' beliefs about how it impacted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 23 publications
2
53
0
1
Order By: Relevance
“…Relatedly, there is a need for work that identifies the specific mentoring tasks or activities that are most effective in providing various types of support and how these activities may be similar or different for different student populations (e.g., older versus younger students and active military/veteran students). Additionally, extending the work of Holt and Berwise (2012) and Behar-Horenstein, Roberts, and Dix (2010), there is a need for research to examine how different groups (e.g., students and mentors of different racial/ethnic groups) experience mentoring.…”
Section: Conceptual Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, there is a need for work that identifies the specific mentoring tasks or activities that are most effective in providing various types of support and how these activities may be similar or different for different student populations (e.g., older versus younger students and active military/veteran students). Additionally, extending the work of Holt and Berwise (2012) and Behar-Horenstein, Roberts, and Dix (2010), there is a need for research to examine how different groups (e.g., students and mentors of different racial/ethnic groups) experience mentoring.…”
Section: Conceptual Issuesmentioning
confidence: 99%
“…Mentoring also directly addresses the need to diversify the STEM disciplines, which have historically not included underrepresented minority students (Perna et al, 2009), and is one of the most prominent efforts to increase the number of individuals from underrepresented groups earning degrees in STEM fields (Behar-Horenstein, Roberts, & Dix, 2010). Supportive mentoring relationships have the potential to increase career ambition and awareness (Parks-Yancy, 2012) and aid students' professional identity development (Murdock, Stipanovic, & Lucas, 2013).…”
Section: Importance and Value Of Mentoringmentioning
confidence: 99%
“…Mentorship of undergraduate students, especially in the Counselling Psychology Quarterly 413 early phase of their research involvement, can be quite time-consuming. Undergraduate students may require more time and engagement from mentors as their research skills are not as developed as those of graduate students (Behar-Horenstein et al, 2010;Brown et al, 2009;O'Clock & Rooney, 1996). Moreover, such mentorship is often not recognized in teaching loads (Thomas & Gillespie, 2008;Wayment & Dickson, 2008), and many URPs do not lead to scholarly publications (Lei & Chuang, 2009).…”
Section: Challengesmentioning
confidence: 96%
“…A number of studies have identified characteristics and functions of mentors that, from the perspectives of students and faculty members, contribute to successful research mentorship (Behar-Horenstein, Roberts, & Dix, 2010;Cox & Androit, 2009;Cramer & Prentice-Dunn, 2007;Shellito, Shea, Mueller-Solger, & Davis, 2001). In a study aimed at understanding how faculty members provide positive mentorship to undergraduate researchers, Shellito and her colleagues (2001) asked students who had engaged in an undergraduate research project (URP) in psychology, biology, physical sciences, mathematics, or engineering to complete a survey on their views and experiences of the research program.…”
Section: Factors Related To Successful Research Mentorshipmentioning
confidence: 97%
“…As argued by Behar-Horenstein et al (2010), students identify a good mentor as one who has "time for the mentee" and listens to the students, while less effective mentors are not readily available to spend time with the students, which forces the students to work independently and depend on postgraduates, technicians, and other students. Limited mentoring does not allow the student to develop a clear understanding of their research and how it will ultimately contribute to the literature (Hunter et al, 2007).…”
Section: Journal Of Geography In Higher Educationmentioning
confidence: 96%